Corruption in contemporary politics a new travel guide - Newell, James L. (Manchester University Press, 2018)
Political corruption is a serious problem. It infringes the rules that define the means of wealth acquisition and the exercise of power, and damages the interests of the advantaged and the disadvantaged alike. For the advantaged wealth cannot be pursued and maintained safely, and for the disadvantaged development is thwarted and resources are redistributed from the poor to the rich.